The nearshore wind and wave energy potential of Ireland: A high resolution assessment of availability and accessibility. (April 2016) - Gallagher, Sarah; Tiron, Roxana; Whelan, Eoin; Gleeson, Emily; Dias, Frédéric; McGrath, Ray
Abstract: A 14-year high resolution wave and wind hindcast was carried out for Ireland. The wind was dynamically downscaled from the ERA-Interim reanalysis to a 2.5 km horizontal resolution and 65 vertical levels, using the HARMONIE meso-scale model. The wave hindcast was derived using WAVEWATCH III on an unstructured grid with resolution ranging between 10 km offshore and 225 m in the nearshore, forced by the downscaled HARMONIE 10 m winds and ERA-Interim wave spectra. The wind and wave hindcasts were thoroughly validated against available buoy data, including wave buoys in nearshore locations and coastal synoptic stations. In addition, the significant wave heights and winds from the hindcasts were compared against all available altimeter data from the CERSAT database at Ifremer. The quality of both the wind and wave hindcasts was found to be good. The wave and wind energy resource in coastal areas was assessed, and discussed in terms of water depth, distance to shore, and seasonal and inter-annual variability. In addition, the current study investigates the nearshore wind and wave climate in conjunction with each other, and highlights two issues with relevance to the ocean renewable energy industry: (i) the complementarity between the wind and wave energy resource, and (ii) the accessibility for marine operations. Our study highlights sites around the Irish coast that might have been overlooked in terms of the potential for wind, wave or combined wind/wave energy installations. Highlights: We produce the highest resolution wind and wave atlas for Ireland, covering the same time period. We examine the energy resource available while taking into account the accessibility levels needed for marine operations. We estimate the complementarity between the wind and wave energy resource in the nearshore around the entire coastline. Our study highlights potential new areas suitable for wave, wind and joint wind-wave renewable energy installations.